2007
DOI: 10.1080/03630260701277057
|View full text |Cite
|
Sign up to set email alerts
|

Two New β0-Thalassemic Mutations: A Deletion (−CC) at Codon 142 or Overlapping Codons 142-143, and an Insertion (+T) at Codon 45 or Overlapping Codons 44-45/45-46 of the β-Globin Gene

Abstract: We report here two new beta(0)-thalassemic mutations. In the first case, a deletion of two nucleotides (-CC) at codon 142 was found in a French Caucasian woman. In the second case, an insertion of a single nucleotide (+T) at codon 45 was found in a Turkish girl. In both cases, no dominant thalassemia-like phenotype was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, our report differs from the previous report in two ways: we performed a family study based on multiple samples; and the carriers and patient showed an elevated level of HbF, which was not observed in the previous case. Ropero et al, 2008), whereas deletions in exon 3 generally lead to a modified C-terminal sequence and to an elongated translation products (Thein, 1992;Lacan et al, 2007). Therefore, this type of mutation usually causes a frameshift in the coding sequence and is classified as b 0 -thalassemia.…”
Section: S U M M a R Ymentioning
confidence: 99%
See 1 more Smart Citation
“…However, our report differs from the previous report in two ways: we performed a family study based on multiple samples; and the carriers and patient showed an elevated level of HbF, which was not observed in the previous case. Ropero et al, 2008), whereas deletions in exon 3 generally lead to a modified C-terminal sequence and to an elongated translation products (Thein, 1992;Lacan et al, 2007). Therefore, this type of mutation usually causes a frameshift in the coding sequence and is classified as b 0 -thalassemia.…”
Section: S U M M a R Ymentioning
confidence: 99%
“…, 2002; Ropero et al. , 2008), whereas deletions in exon 3 generally lead to a modified C‐terminal sequence and to an elongated translation products (Thein, 1992; Lacan et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%